An Evidence-Based Review: The Effects of Malaysian Traditional Herbs on Osteoporotic Rat Models - Mohammad N.A.; Razaly N.I.; Mohd Rani M.D.; Muhammad Shamsir Mohd Aris; Nadia M.E. (Penerbit Universiti Sains Malaysia, 2024)
Indexed by WOS/SCOPUS